Živi, želi, ljubi: pomenska polja intimnosti v slovenski in srbski prozi fin de siècla - Mandić, Lucija; Ilin, Darko (Slavia Centralis, 2024)
The present paper analyses emotional and physical intimacy in Slovenian and Serbian prose from the late 19th to the early 20th century using word embeddings. Given the complexity of defining intimacy, we consider a broad range of relationships depicted in fin de siècle literature. The Word2Vec language model identifies eight semantic fields encompassing platonic and sexual relationships, including violence, since it seems to be semantically closely related to sexuality in the analysed literary works. Through a comparative study, notable differences between Serbian and Slovenian prose are established. Additionally, the article examines how these semantic fields manifest in works by male and female authors, providing insights into societal perceptions of intimacy and gender socialization.